Presence and Performance as a Function of Teammate Agency and Individual Differences in a Video Game. (September 2015) - Proaps, Alexandra B.; Long, Shelby K.; Cowan, Magan; Sandberg, Hilary M.
Past research has examined the effects of agency on human performance and affect (e.g., Nowak & Biocca, 2001; Weibel et al., 2008), but results and design recommendations are still inconclusive. The purpose of the current study was to investigate the individual differences in video game efficacy, immersive tendency, avatar characteristics, and the way avatars impact presence and performance within a game-based training environment. Twenty six college students were told they were working with either a computer-programmed teammate or a human teammate who provided information about how to complete twelve specific tasks in a first-person shooter game, Arma 3 TM . Mean comparisons indicate some differences in performance and presence as a function of teammate agency, but none of these differences were statistically significant due to low observed power. We conclude that this common method of manipulating teammate agency in the literature may not be salient for some tasks.